Improving Pronunciation Skills by Learning the Different Sounds of Regular Past Tense Verbs in Popular Song Lyrics - Sari, Sulhizah Wulan; Qhairunissa Juwita Amalia; Aathifah Keyssa Tatsbita Putri; Alifa Laragita; Julia Rahmallah Zahrah (International Journal of English and Applied Linguistics (IJEAL), 2025)
Pronunciation skills are a crucial component of effective oral communication, particularly for EFL learners. This study examines the challenges faced by English as a foreign language (EFL) learners when pronouncing words ending in -ed. It also explores whether explicit instruction on the pronunciation rules of -ed endings can improve learners' pronunciation skills. Five learners who graduated from the same senior high school participated in the research. Using a descriptive qualitative approach, the study employed two pronunciation tests (pre- and post-tests) and utilized popular songs containing words with -ed endings as learning media. The research focused on students' ability to pronounce the three correct-ed sounds (/d/, /t/, and /?d/) based on the final consonant of the base word. After receiving explicit instruction, learners showed significant improvement, particularly in distinguishing and pronouncing the sounds correctly. Most participants reduced their pronunciation errors and obtained a clearer understanding of the rules. These findings suggest that combining rule-based instruction with engaging materials like song lyrics can be effective in improving pronunciation.